MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MELIPAT KERTAS ANAK USIA 4-5 TAHUN DI KB TUNAS HARAPAN DESA KOTO PERAMBAHAN KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR - Nurhidayah Nurhidayah; Isjoni Isjoni; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase fine motor skills in children aged 4-5 years through paper folding activity in KB Tunas Harapan village Koto Perambahan Kampar District Kampar Regency East. This study is je nis studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years, amounting to 15 children at KB Tunas Harapan. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that the activity of folding paper can improve fine motor skills in children aged 4-5 years. It can be seen from the increase in the average percentage of fine motor skills children in the first cycle of 54.86% which is the criteria began to develop (MB) and an increase of 48.61% in the second cycle be 81.53% which is very good at developing criteria (BSB). Thus, activity of folding paper can improve fine motor skills of children aged 4-5 years in KB Tunas Harapan village Encroachment Koto Kampar District Kampar Regency East.Keywords : Fine Motor Skill, Folded Paper activities